ASSESSING THE IMPACT OF EMPLOYEE SKILLS AND TRAINING ON EMPLOYEE PERFORMANCE THROUGH THE MODERATING ROLE OF EMOTIONAL MANAGEMENT - Meilaty Finthariasari; Mella Widdia (Universitas Muhammadiyah Bengkulu, 2026)
This study examines the effects of employee skills and training on employee performance, with emotional management serving as a moderating variable, at PT Bio Nusantara Teknologi Bengkulu. A quantitative survey approach was employed, with data collected through questionnaires distributed to permanent employees. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that employee skills and training have a positive and significant effect on employee performance. Emotional management also significantly influences employee performance. Furthermore, moderation analysis reveals that emotional management strengthens the relationship between employee skills and employee performance but does not moderate the relationship between employee training and employee performance. These findings suggest that employee skills and job-relevant training are important determinants of performance improvement. In addition, employees’ ability to manage their emotions enhances the contribution of skills to performance, highlighting the importance of emotional management in the workplace